Cooperating Teachers’ Best Practices for Mentoring #4: Role Modeling - Heather R. Nesbitt; Debra M. Barry (EDIS, 2022)
This fourth publication of the Cooperating Teachers’ Best Practices for Mentoring series focuses on role modeling. Role modeling is achieved by the cooperating teacher positively modeling all aspects of teaching. This can be accomplished through demonstrating teaching methods, explaining classroom management techniques, and modeling effective communication. Through observation, the student teacher decides what and how they will implement or not implement as an educator in their own classroom. Written by Heather R. Nesbitt and Debra M. Barry and published by the UF/IFAS Department of Agricultural Education and Communication; 3 pp. https://edis.ifas.ufl.edu/wc423